2019
DOI: 10.1186/s12874-019-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the WHOQOL-BREF among Norwegian substance use disorder patients

Abstract: Background Quality of life (QoL) is an established outcome measure of substance use disorder treatment. The WHOQOL-BREF is the gold standard tool, but its appropriateness for particularly vulnerable patient populations must be further explored. This article examines the scaling qualities of the WHOQOL-BREF in a Norwegian substance use disorder population, and explores relationships with social and health variables. Methods 107 participants in a larger national treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 68 publications
(65 reference statements)
1
23
0
2
Order By: Relevance
“…The brief WHO Quality of Life Assessment (WHOQOL-BREF) was used to assess patients' QOL (1). It has been validated in patients with SUDs (14,46). WHOQOL-BREF is a self-reported scale composed of 26 items, in which item 3 to 26 constitutes the individual's four domains of QOL, namely physical QOL (PHYSQOL, seven items), psychological QOL (PSYCHQOL, six items), social QOL (SOCIALQOL, three items) and environmental QOL (ENVIRQOL, eight items).…”
Section: Quality Of Lifementioning
confidence: 99%
“…The brief WHO Quality of Life Assessment (WHOQOL-BREF) was used to assess patients' QOL (1). It has been validated in patients with SUDs (14,46). WHOQOL-BREF is a self-reported scale composed of 26 items, in which item 3 to 26 constitutes the individual's four domains of QOL, namely physical QOL (PHYSQOL, seven items), psychological QOL (PSYCHQOL, six items), social QOL (SOCIALQOL, three items) and environmental QOL (ENVIRQOL, eight items).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Since health-related quality of life reflects physical health, mental health, modern social and emotional health conditions, and both the disease state and also the psychological and social functional effects of the disease ( 25 ), health-related quality of life is affected by many factors ( 26 ). This study further analyzed the factors affecting the health-related quality of life of BC patients’ spouses and found that the social support and cognitive factors of treatment effects were influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…The WHOQOL has been verified to be reliable and valid in Korea [ 2 ], and it is a relatively proven evaluation method frequently used in other studies [ 3 - 5 ]. It can be used to compare the evaluation results by country.…”
Section: To the Editormentioning
confidence: 99%